A mini‐review of procedural sedation and analgesia in the emergency department. Issue 1 (6th October 2020) - Homma, Yosuke; Norii, Tatsuya; Kanazawa, Takeshi; Hoshino, Atsumi; Arino, Satoshi; Takase, Hiroshi; Albright, Danielle; Funakoshi, Hiraku; ,
Abstract : Procedural sedation and analgesia (PSA) is performed for a variety of indications in emergency departments (EDs). Although the practice of PSA in the ED is somewhat unique from other clinical areas, there is currently no guideline for this practice in Japan. Policy statements and guidelines for PSA have been published in Europe and North America. These guidelines suggest first evaluating patients carefully before performing PSA, and then deciding on target sedative level and choice of medications. Patient evaluation requires a combination of continuous visual observation by trained medical staff to assess the depth of sedation and respiration with noninvasive measurements of blood pressure, continuous electrocardiography monitoring, and pulse oximetry. Sedative selection should be based on its characteristics, peak time, effectiveness, and risks. It is important to administer sedatives and analgesics in small, incremental doses while keeping a close eye on the patient's reaction to avoid adverse events (AEs) until the planned sedation level is reached. Further, additional attention is needed for special populations such as pediatric and elderly patients. PSA is a key element for patient‐centered care in emergency medicine. In this manuscript, we review the available evidence for PSA in the EDs, including guidelines for evaluation, monitoring, pharmacology, AEs, and special populations such as pediatric and elderly patients. Abstract : Procedural sedation and analgesia (PSA) is a key element for patient‐centered care in emergency medicine. In this manuscript, we review the available evidence for PSA in the emergency department, including guidelines for evaluation, monitoring, pharmacology, adverse events, and special populations such as pediatric and elderly patients.